Biblioteki i księgozbiory w Bydgoszczy w okresie zaborów. Zarys dziejów (Kronika Bydgoska, 2012)
The article is an attempt to depict synthetically the history of Polish and German libraries in Bydgoszcz in the years 1772-1920. The sources are archives, library catalogues, address books, articles and press announcements. In the early 19th century, church, office and school libraries existed in Bydgoszcz. Monasterial libraries were dispersed in connection with disbandment. However, with the passage of time new types of libraries appeared, i.e. education, specialist, and scientific libraries. Among them, there were book collections of all type associations and organisations: scientific, education, professional, religious, and political. When bookselling started to develop on a larger scalę in the early 19th century, paid lending libraries and reading rooms appeared. The first public library was established in the early 20,h century.